ASSESSMENT OF POTENTIAL MARINE CURRENT ENERGY IN THE STRAITS OF THE LESSER SUNDA ISLANDS - Ai Yuningsih; Mario D. Saputra (Marine Geological Institute of Indonesia, 2021)
The Lesser Sunda Islands extend from Bali to Timor and consist of two geologically distinct parts formed by a subduction system of oceanic crust along the Java-Timor Trench. The northern part which includes Bali, Lombok, Sumbawa, Flores, Wetar, Pantar and Alor, is volcanic in origin; whilst the southern part is non-volcanic, encompassing the islands of Sumba, Timor and Rote. The straits along the Lesser Sunda Islands are formed as a result of very complex geological processes and tectonics in this area. These straits are the most important cross-sections in the southern part of the Indonesian Throughflow (ITF), functioning as outlets for the mass flows of seawater from the Pacific Ocean to the Indian Ocean through the Flores and the Savu Seas. In these straits, relatively high current speeds are occurred, not only caused by the ITF but also due to its geometry, the influence of tidal flow, and monsoonal currents.Site study and ocean current measurement were conducted by using an echosounder, a pair of Acoustic Doppler Current Profilers (ADCP), and other supporting equipment. In general, the average of most ocean current speeds is less than 1.5 m/s with a duration flow of 8 -12 hours a day, and the maximum speed reaches up to 3 m/s. The tidal types in almost all the straits are mixed semidiurnal tides, in which two high waters and two low waters occur twice a day, with the high and low tides differ in height.The Lesser Sunda Straits were selected as the potential sites for ocean current power plant because their current speeds are relatively high and their characteristics are more predictable compared with other straits from other regions. Based on the results of bathymetry survey and current characteristics from the deployed ADCP at a fixed (stationary) location on the seabed, the best location for the current power turbines is at the depth of 15-30 m where the seabed gently sloping.